Genetic Diversity of Great Plains Hard Winter Wheat Germplasm for Forage. Issue 5 (1st September 2016) - Kim, Ki‐Seung; Anderson, Joshua D.; Newell, Mark A.; Grogan, Sarah M.; Byrne, Patrick F.; Baenziger, P. Stephen; Butler, Twain J.
Abstract : Wheat ( Triticum aestivum L.) has been widely grown for winter forage production across the world. However, improvement of forage yield and nutritive characteristics has not been a major goal of wheat breeding programs, and little is known about genetic diversity in the traits of winter wheat germplasm. A set of 299 hard winter wheat germplasm from the Great Plains was evaluated during two growing seasons in Oklahoma and 15 forage‐related traits were evaluated. There were significant ( P < 0.0001) genetic variations in all the traits but effects of environment and germplasm × environment interaction were significant for seven and eight traits, respectively. A significant portion of the variation for forage traits was due to genetics, indicating an ability to breed for improved forage traits. Dry matter yield (DMY, kg ha −1 ) of the germplasm ranged from 1260 for Cheyenne to 4158 for Sturdy2K. Crude protein (CP, g kg −1 ) ranged from 161 for OK05108 to 268 for Nuplains. When crude protein yield (kg ha −1 ) was considered, Sturdy2K was the best germplasm, followed by 2180 and OK1068009. State of origin of the germplasm was also a significant source of variation for most of the traits. Heading date was positively and negatively associated with CP and DMY, respectively. This study identified significant genetic variations of the hard winter wheat germplasm for forage traits and the results of this study could provide useful guidelines for winter forage wheat breeding programs.